STUDY ON SURFACE STRENGTHENING OF TC4 TITANIUM ALLOY BLADE WELD BASED ON ELECTRON BEAM WELDING - WANG Zhen; YU LuoSheng; CHEN Long; MENG XiangZhi; LI QingYu (Jixie qiangdu)
The overall performance of aeroengine blades greatly affects the safe and stable operation of the aircraft. In this paper,after electron beam welding of TC4 titanium alloy blades of an aero-engine,fatigue cracks often appear in the welding seam during service,which lead to the failure of the blades. Combined with X-ray diffraction method and finite element simulation analysis results. The distribution of residual stress in welding seam and surrounding area of titanium alloy blade was studied and analyzed,and the change of residual stress before and after strengthening was explored. The experimental results show that the tensile stress appears on the weld seam and the surface of the surrounding area,and the vertical weld direction stress value is about + 36 MPa after welding;after strengthening,there is a large and uniform compressive stress on the surface,and the stress value is about-200 MPa. The results of finite element simulation show that the blade surface changes from tensile stress to compressive stress,and the stress state is improved obviously,and then the fatigue resistance of blade is improved. It provides theoretical basis and technical reference for anti-fatigue manufacturing of aeroengine blade surface.